Morphological Alterations In Blood Crystals Under The Influence Of Heavy Metals: A Comparative Study In Three Experimental Groups - Israyiljanov Saminjan; Mamasaidov Jamoldin; Abdulbokieva Khilola (International Journal of Medical Sciences And Clinical Research, 2025)
In recent years, the impact of heavy metals in the environment on animal and human health has received considerable attention. Heavy metals can adversely affect various physiological systems, including the hematological system. This study investigated structural changes in blood plasma in the form of crystal morphology resulting from exposure to heavy metals. The toxic effects of lead, mercury, cadmium, and cobalt on animal organisms were assessed. During the study, the effects of heavy metals on blood composition, red blood cells, their morphology, and functions were analyzed. In this study, juvenile male Wistar rats, weighing 60–70 g, were administered a diet containing heavy metals for a duration of 21 days. At the end of this period, blood samples were collected from the animals and analyzed under laboratory conditions. The shape of erythrocytes, their aggregation, and signs of hemolysis were examined. Additionally, changes in the color and density of blood plasma were recorded. Morphological alterations in blood crystals were analyzed as indicators reflecting the physiological impact of heavy metals. In the experimental groups, alterations in the morphology of blood crystals were observed. In blood samples from lead-exposed rats, large and irregular protein aggregates appeared in the central zone, symmetry was disrupted in the radial area, and uneven fissures were observed in the periphery. In rats exposed to mercury, deposits were observed in the central zone, interrupted lines in the radial area, and large crystals formed in the periphery. The number of crystals in the blood of exposed animals increased significantly. In the control group, blood crystals were normal, flat, and disk-shaped, with no deformation or aggregation observed. Blood crystals in healthy rats were ordered and smooth, indicating preserved protein–electrolyte balance. In the lead- and mercury-exposed groups, central aggregates, radial disruptions, and irregular peripheral crystals reflected disturbed protein–lipid balance and impaired cellular metabolism. These results indicate that blood crystal morphology can serve as a sensitive and diagnostic tool for evaluating toxic stress and the effects of heavy metals.